INVESTMENT COMPONENTS EMBEDDED IN SG&A EXPENSES: COST STICKINESS AND MARKET REACTIONS - Jems Arison Zacharias; Herry Aprilia Manubulu; Christian Agustinus Besi (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study examines differences in the degree of cost stickiness between investment and operating selling, general, and administrative (SG&A) expenses and market reactions from each component in Indonesian technology firms. The sample comprises 167 firm-year observations over the 2020–2024 period. Hypotheses are tested using multiple linear regression based on the cost stickiness model of Anderson and the market reaction model of Weiss. The results indicate that SG&A expenses exhibit cost stickiness, whereby costs adjust more slowly when revenues decline than when revenues increase. Furthermore, investment SG&A demonstrates a significantly higher degree of cost stickiness than operating SG&A. In addition, cost stickiness arising from investment SG&A significantly moderates the relationship between earnings forecast errors and market reactions, whereas cost stickiness associated with operating SG&A does not exhibit a significant moderating effect. These findings suggest that although the market partially recognizes the investment component of SG&A as intangible assets, information limitations reduce market responsiveness to the long-term implications of investment cost stickiness. This study provides implications for investors and analysts in evaluating the performance of technology-based firms in Indonesia.